Penggunaan media evaluasi pembelajaran berbasis game edukasi Kahoot pada hasil belajar sejarah di SMAN 51 Jakarta - Ardhy Yuwono; M Fakhruddin; Nurzengky Ibrahim (Historiography: Journal of Indonesian History and Education, 2022)
This research aims to determine the effect of using Kahoot educational game-based learning evaluation media on student learning outcomes in history subjects at SMA Negeri 51 Jakarta. The study uses quantitative research methods with experimental research. The results showed that students in the experimental class (class XI IPS 3) learned more than students in the control class (class XI IPS 2), with the average value of learning outcomes in the experimental class (XI IPS 3) of 89.53, while the average value of the control class learning outcomes (XI IPS 2) was 76.7. This shows that there is an effect on the use of learning evaluation media based on kahoot! An educational game for the learning outcomes of students in the history subject of Jakarta 51 High School.Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media evaluasi pembelajaran berbasis game edukasi Kahoot terhadap hasil belajar siswa pada mata pelajaran sejarah di SMA Negeri 51 Jakarta. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian eksperimen. Hasil penelitian menunjukkan bahwa nilai rata-rata hasil belajar siswa kelas eksperimen (XI IPS 3) lebih besar daripada nilai ratarata hasil belajar siswa kelas kontrol (XI IPS 2), di mana nilai rata-rata hasil belajar kelas eksperimen (XI IPS 3) sebesar 89.53, sedangkan nilai rata-rata hasil belajar kelas kontrol (XI IPS 2) sebesar 76.7. Hal ini menunjukkan bahwa terdapat pengaruh penggunaan media evaluasi pembelajaran berbasis game edukasi Kahoot terhadap hasil belajar siswa pada mata pelajaran sejarah di SMA Negeri 51 Jakarta.